Effects of dietary vitamin C and E supplementation on exercise-induced muscle damage among young Kelantan weightlifter - Mohammed, S. M.; Jawis, M. N.; Ahmed, S. A.; Krasilshchikov, O. (Biology of Exercise, 2015)
It has been hypothesized that markers of oxidative stress and muscle damage induced by weightlifting training could be decreased by supplementing subjects with dietary vitamin C and E. Hence, this study was carried out to invistigate the effects of dietray vitamin C and E supplementation on oxidative stress and muscle damage markers among male and female weightlifters in Kelantan state, Malaysia. For this purpose, thirty two trained weightlifters were recruited and randomly assigned into two groups. The supplement group (n=16, 16.5± 2.2 years of age, 162.2 ± 10.4 cm of height, 65.7 ± 26.1 kg of body weight) was given 500 mg of vitamin C and 400 IU of vitamin E per day, while the placebo group (n=16, 15 ± 1.7, 162.2 ± 10.4 cm, 61.5 ± 13.9 kg accordingly) was given maltodextrine, zero calorie per day for 6 weeks. The following parameters were measured before and after intervention to detect the effects of supplementation: muscle circumferernce of mid-upper arm and calf, serum creatine kinase (CK ), lactate dehydrogenase (LDH) and urinary thiobarbituric acid reactive substances (TBAR S). Data was expressed as median and interquartile at p < 0.05. There were no significant effects (p>0.05) of dietary vitamin C and E supplementation on the muscle damage markers, CK and LDH, as well as on oxidative stress markers through urinary TBAR S analysis, when the two study groups were compared. These results indicated that vitamin C and E were not effective in ameliorating markers of muscle damage and oxidative stress induced by weightlifting training. It might be possible that these weightlifters already have acquired protection, both structurally and biochemically, resulting from chronic exposure to weightlifting training.